2021
DOI: 10.1128/msphere.00287-21
|View full text |Cite
|
Sign up to set email alerts
|

Skin Metagenomic Sequence Analysis of Early Candida auris Outbreaks in U.S. Nursing Homes

Abstract: Candida auris is a human pathogen of high concern due to its extensive antifungal drug resistance and high mortality rates associated with invasive infections. Candida auris skin colonization and persistence on environmental surfaces make this pathogen difficult to control once it enters a health care facility. Residents in long-term care hospitals and nursing homes are especially vulnerable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
(55 reference statements)
2
24
0
Order By: Relevance
“…The final US study (submitted to SRA in 2020) was conducted within hospital settings and found a very high number of reads of C. auris sequences on human skin samples (33), in agreement with previous reports from hospital settings (34).…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…The final US study (submitted to SRA in 2020) was conducted within hospital settings and found a very high number of reads of C. auris sequences on human skin samples (33), in agreement with previous reports from hospital settings (34).…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…Briefly, genomic DNA was isolated from stool samples using the Qiagen QIAamp® PowerFecal® Kit, per the manufacturer’s protocol. For skin samples, MasterPure yeast DNA purification kit (Lucigen Corp. Middleton, WI) and Genomic DNA Mini Kit (Invitrogen, Carlsbad, CA), lysis buffer with the addition of 1ul (3500 U) of diluted Ready Lyse solution were used according to the manufacturer’s protocol [ 36 ]. Yield and purity of isolated DNA were confirmed by Qubit analyzer (Invitrogen, Carlsbad, CA) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…C. auris outbreaks also highlight the need to understand the skin mycobiome in this context. Huang and colleagues utilized metagenomic sequencing to characterize the skin microbiome of skilled nursing facility patients during a C. auris outbreak [9]. They found the patients in the outbreak facility were more likely to harbor a variety of Candida spp., when compared to individual residing in a non-outbreak facility, whose mycobiomes were more likely to be dominated by Malassezia.…”
Section: How Can These Models Be Used For Future Study?mentioning
confidence: 99%
“…This pathogenicity pattern distinguishes C. auris from other Candida species, including Candida albicans, which typically reside as commensals in the gastrointestinal tract prior to the development of disseminated disease.C. auris frequently colonizes the axilla and groin, sites typically sampled in the screening of patients for resistant bacteria, including methicillin-resistant Staphylococcus aureus [9][10][11]. However, a broader investigation of residents in a skilled nursing facility identified C. auris colonization across 10 different body sites, with frequent colonization of 2 or more areas [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation